Способ настройки системы компенсации магнитного поля распределительного устройства - Лупиков, Валерий Сергеевич (НТУ "ХПИ", 2003)
Рассмотрена структура параметрической системы автоматической компенсации внешнего магнитного поля, создаваемого токопроводами силовой цепи распределительного устройства вблизи его поверхности. Предложен способ настройки параметров электромагнитов-компенсаторов системы по данным магнитных измерений. Применение такой системы позволяет эффективно компенсировать магнитное поле до уровня, отвечающего требованиям электромагнитной совместимости.

The structure of parametrical system for automatic compensation of the external magnetic field created by conductors of the switchboard power circuit near to its surface is considered. The method providing adjustment of the system electromagnets-equalizers parameters is offered according to magnetic measurements. Application of such system allows effectively compensate the magnetic field up to a level which is meeting the requirements of electromagnetic compatibility.
Method providing adjustment of swit-board system for compensation of its magnetic field
Keywords: токопроводы; силовые цепи; распределительное устройство; магнитные измерения; электромагнитная совместимость; электромагниты; компенсаторы; switchboard; power circuit; external magnetic field; electromagnets-equalizers; adjustment